From the state’s development promise to the uncertain lives of farmers in eastern Thailand - Benjanavee, Kampanart (Humanities, Arts and Social Sciences Studies, 2024)
This research paper aims to examine the state’s development promise in relation to the Eastern Economic Corridor development (EEC) project and its impact on people’s livelihoods. The study utilized a qualitative approach and ethnographic research to collect data on the operation of the EEC project and its impact on people’s livelihoods. The key informants, who were actively involved in the movement for farm safety, were 25 farmers from a farmers network in Kabinburi district, Prachinburi province, and Phanom Sarakham district, Chachoengsao province. The study found that the EEC project has been a crucial development undertaking in Thailand since 2017. The Thai state has promised that the EEC project will provide a better future for the people, stating that the operation of the project will focus on investing in infrastructure, providing investment privileges, eliminating investment barriers, and establishing a centralized authority. However, the local people’s experiences with the EEC project demonstrate the formation of unequal power relations that have led to an uneven distribution of the project’s benefits. Although local communities are hopeful that the EEC project will provide access to new markets, they still fear the uncertainty of their lives due to various state mechanisms established in the project, which prevent them from participating in the local decision-making process. Some local farmers have experienced an expansion of factories and waste disposal plants, causing fear of pollution on farms, and other non-agricultural land use activities in the EEC backyard, or peripheral areas of the EEC project.